The impact of free GP care on the utilisation of GP services in Ireland: An evaluation of different approaches - Paul K. Gorecki (The Economic and Social Research Institute (ESRI), 2016)
The successful implementation of free GP care for all private patients in Ireland requires an estimate of the likely change in the number of GP visits occasioned by this policy so as: (i) to set the capitation fee; and (ii) to ensure adequate supply of GPs is in place. The paper examines two methodologies to derive such estimates: retrospective patient self-reporting or recall (e.g. Growing Up in Ireland, The Irish Longitudinal Study on Ageing); and, GP practice records. Estimates based on six GP practices by Behan (2013, 2014) substantial overestimate of the likely impact of free GP care. McGovern's (2015) more recent estimates for the HSE, based on patient recall, used in forecasting future demand for GPs to 2025 also appear to be biased upward. The underlying studies, assumptions and papers are not, however, cited. This should be corrected. A proper debate and discussion can then take place concerning the optimal phasing in of free GP care.
Keywords: H51; I12; I18; 330; GP visits; Medical Card; GP Visit Card; Free GP Care; under 6s